Effect of Trust, Quality of Service to Jne Express Consumer Satisfaction in Sampit District, Kotawaringin Timur District - Hayati*, Sari; Andriyati, Yuli; Handayani, Leni (Universitas Syiah Kuala, 2024)
The purpose of this study was to determine the factors that influence consumer satisfaction with JNE Express freight forwarding services in Sampit District, Kotawaringin Timur. District, in the study of 100 people using the Slovin formula. By using the Accidental Sampling method. With the provisions of the data analysis in this study is quantitative using multiple linear regression method and the data is analyzed using the SPSS V.23 program. Based on the results of this study indicate that Trust and Service Quality significantly influence Consumer Satisfaction in JNE Express freight forwarding services in Sampit District, Kotawaringin Timur Regency. Simultaneously the independent variable (Trust and Service Quality) significantly influences the dependent variable (Customer Satisfaction) on JNE Express freight forwarding services in Sampit District, Kotawaringin Timur Regency. R Square value of 0.571 or 57.1% means the variable Customer Satisfaction is influenced by the Trust and Quality of Consumers while the remaining 42.9% is influenced by other variables not used in this study.